Value and features of recognition in criminal processual evidence - Rohatynska, Nina; Kuibida, Adriana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The research covers the peculiarities of obtaining and admissibility of evidence in criminal proceedings. The scientific approaches were analyzed to define the concept of evidence as the main legal category in criminal proceedings.